Activity of Bay y3118 against quinolone-susceptible and -resistant gram-negative and gram-positive bacteria. - Piddock, L J (1994)
The activity of Bay y3118 against laboratory strains of bacteria, including those with mutations in gyrA, with decreased expression of outer membrane proteins, and/or that are multiply resistant, and 121 selected clinical isolates, including highly fluoroquinolone-resistant bacteria from Spain and Argentina, was determined. Bay y3118 was extremely active (MICs, < or = 1 microgram/ml) against all bacteria, including quinolone-resistant laboratory strains. However, Bay y3118 was less active against 46 of 121 quinolone-resistant clinical isolates, such that > or = 16 micrograms of Bay y3118 per ml was required to inhibit 3 isolates. The concentration of Bay y3118 required to inhibit DNA synthesis by 50% correlated well with the MIC. Bay y3118 had accumulation kinetics similar to those of previously studied fluoroquinolones, e.g., ciprofloxacin, and there was a 50% decrease in the steady-state concentration in those members of the family Enterobacteriaceae that lacked porin proteins. Magnesium chloride at 20 mM apparently abolished the accumulation of Bay y3118 into Escherichia coli and reduced the level of accumulation into other gram-negative bacteria and Staphylococcus aureus. Carbonyl cyanide m-chlorophenylhydrazone at 100 microM enhanced the accumulation of Bay y3118 into E. coli, but it had a minimal effect on accumulation into S. aureus.